Proteomic profiling of small extracellular vesicles from bovine nucleus pulposus cells - Ankita Samanta; Mi-Jeong Yoo; Jin Koh; Sina Charlotte Lufkin; Thomas Lufkin; Petra Kraus (PLoS ONE, 2025)
Small extracellular vesicles (small EV) are a conserved means of communication across the domains of life and lately gained more interest in mammalian non-cancerous work as non-cellular, biological therapeutic with encouraging results in recent studies of chronic degenerative diseases. The nucleus pulposus (NP) is the avascular and aneural center of an intervertebral disc (IVD), home to unique niche conditions and affected in IVD degeneration. We investigated autologous and mesenchymal stem cell (MSC) small EVs for their potential to contribute to cell and tissue homeostasis in the NP niche via mass spectrometric proteome and functional enrichment analysis using adult and fetal donors. We compared these findings to published small EV databases and MSC small EV data. We propose several mechanisms associated with NP small EVs: Membrane receptor trafficking to modify signal responses promoting niche homeostasis; Redox and energy homeostasis via metabolic enzymes delivery; Cell homeostasis via proteasome delivery and immunomodulation beyond an association with a serum protein corona. The proteome signature of small EVs generated by NP parent cells is similar to previously published small EV data, yet with a focus on supplementing anaerobic metabolism and redox balance while contributing to the maintenance of an aneural and avascular microniche.